Twentieth-Century Mosque Architecture in East Asia: The Case of Taipei’s Grand Mosque (Senibina Masjid abad ke-20 di Asia Timur: Kes Masjid Besar Taipei) - Broilo, Federica A. (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
Islam was introduced to Taiwan in two different periods via migrations of populations from the continent. The first one occurred in the seventeenth century in the wake of Ming loyalist Zheng Chenggong’s campaign of resistance against the Qing. The later one was in the mid-twentieth century following Chiang Kai-shek’s retreat to Taiwan after the defeat of the Nationalists in the Civil War against the Communist Party. Taipei’s Grand Mosque was built in 1960 following the second migration of Muslim population from mainland China. At the end of the 1950s, the Chinese Muslim Association (CMA) in Taiwan commissioned the construction of Taipei’s Grand Mosque to Chinese architect Yang Cho-cheng. The building, inaugurated in 1960 in front of several leaders of the Muslim world, is an architectural anomaly in Taipei’s urban landscape and it has strangely been overlooked by the most relevant contemporary western literature on building mosques in non-Muslim countries. Three important mosques were built in non-Muslim countries in the first half of the twentieth century: the Jamia Mosque in Hong Kong (1915); the Kobe Mosque (1935); and the Old Tokyo Mosque (1938) in Japan. At first glance, Taipei’s Grand mosque is immediately recognizable to the general public as a temple of Muslim faith, because it features elements traditionally associated with mosques, such as the dome, and the two slender minarets. For its design, the architect Yang Cho-cheng combined several Islamic architectural traditions (Umayyad, Fatimid, Safavid, and Ottoman) with new building techniques like the use of reinforced concrete. Even if it might look like some sort of architectural pastiche, it is actually the manifesto of the foreign politics of Taiwan in the 1960s. The following article is a detailed architectural analysis of Yang Cho-cheng’s Grand Mosque and all the factors which led to its peculiar design. Keywords: Taiwan, Islam, Islamic Architecture, Taipei, Mosque design, 1960s. Abstrak Islam diperkenalkan ke Taiwan dalam dua tempoh yang berbeza melalui migrasi penduduk dari benua itu. Yang pertama berlaku pada abad ketujuh belas semasa kempen penentangan Ming Zheng Chenggong terhadap Qing. Yang kemudiannya adalah pada pertengahan abad kedua puluh selepas berundurnya Chiang Kai-shek ke Taiwan selepas kekalahan Nasionalis kepada Parti Komunis dalam Perang Saudara. Masjid Besar Taipei dibina pada tahun 1960 berikutan penghijrahan kedua penduduk Islam dari tanah besar China. Pada penghujung tahun 1950-an, Persatuan Cina Islam (CMA) di Taiwan telah menyerahkan kerja pembinaan Masjid Besar Taipei kepada arkitek Cina bernama Yang Cho-cheng. Bangunan yang dirasmikan pada tahun 1960 di hadapan beberapa pemimpin dunia Islam, adalah anomali seni bina lanskap di bandar Taipei tetapi ironinya kesusasteraan barat kontemporari seperti tidak mengiktiraf pembinaan masjid-masjid di negara bukan Islam. Terdapat tiga buah masjid penting yang telah dibina negara bukan Islam pada separuh tahun pertama abad kedua puluh: Masjid Jamia di Hong Kong (1915); Masjid Kobe (1935); dan Masjid Tokyo Lama (1938) di Jepun. Sekilas pandang, masjid Grand Taipei diketahui oleh masyarakat umum sebagai tempat pengibadatan orang Islam, kerana ia mempunyai unsur-unsur tradisi sebuah masjid, seperti mempunyai kubah, dan dua batang menara yang tinggi. Dalam reka bentuk senibinanya, arkitek Yang Cho-cheng telah menggabungkan beberapa tradisi seni bina Islam (Umayyad, Fatimid, Safavid, dan Uthmaniyyah) dengan teknik bangunan baru seperti penggunaan konkrit bertetulang. Walaupun ia kelihatan seperti sejenis karya senibina, ia sebenarnya adalah manifesto politik asing Taiwan pada tahun 1960-an. Artikel ini bertujuan menganalisa seni bina dengan terperinci mengenai Masjid Besar yang dibina oleh Yang Cho-cheng dan semua faktor yang membawa kepada keunikan reka bentuk seni binanya. Kata Kunci: Taiwan, Islam, Arkitek Islam, Taipei, Rekabentuk Masjid, 1960s.